Prevalence and factors associated with Frailty Syndrome in elderly people in Joinville - Peres, Breno Roberto (2023)
INTRODUCTION: With the aging of the Brazilian population, to scale and evaluate the profile of the vulnerable population for having the Frailty Syndrome in Elderly (FSE) and understanding its associated factors is of great importance. OBJECTIVE: To analyze the profile of elders corresponding to the information referred in the frailty indicators on the Edmonton Frail Scale on a geriatric specialized facility. METHODOLOGY: The present study is a cross-sectional, analytical study, with the elders from a geriatrics specialized facility in Joinville, Brazil. It was analyzed the social-economic profiles (gender, ethnicity, income and schooling) and the evaluation for the FSE, as well as comorbidities present. The project has been approved by the Ethics in Research Committee of UNIVILLE under the protocol number 40940020.6.0000.5366. RESULTS: the results were obtained from the 141 elderly interviewed, with 74 years old as the average age. Majority (60%) female, white (90,2%), of low scholar education (56%) and married or in a stable relationship (53,2%). The prevalence of some sort of fragility was of 17,7% (IC95%). DISCUSSION: Although the discussion over the criteria to establish FSE, the present study was based on the Edmonton Frail Scale. The local sample analyzed demonstrated how the discussion over schooling, smoking, income and the high rates of comorbidities predisposes to FSE and, in that way, also in a higher prevalence of elderly falls. This aligns with previous literature studies which showcase higher prevalence of falls in patients with these epidemiological characteristics. CONCLUSION: Despite some limitations of this present study, such as it being done in a well respected specialized geriatric facility, it does demonstrate the local profile of the elderly stricken with FSE.